PERANCANGAN BACKEND MODULAR DAN REUSABLE UNTUK SISTEM SUPER ADMIN PADA APLIKASI LOMBOK HALAL ROOM DENGAN RESTFUL API - Muhamad Singgih; Royana Afwani; Ramaditia Dwiyansaputra; Mochammad Dinta Alif Syaifuddin (Universitas Budi Luhur, 2026)
The growth of halal tourism in Lombok, Indonesia, calls for scalable digital platforms with strong and centralized administrative governance. This study proposes and implements a domain-oriented, modular RESTful API backend to support Super Admin operations in the Lombok Halal Room (LHR) platform. Using a design-science approach and an iterative SCRUM process, we developed a layered API Service Repository Infrastructure architecture using Hapi.js, PostgreSQL, and Redis, delivering 42 endpoints across key administrative domains with uniform JSON contracts and JWT-based authentication. The proposed contribution is a metric-driven engineering template that links SCRUM execution to modular backend domains and validates the resulting system using performance and software-quality measurements. Experimental results under controlled workloads show that Redis caching substantially improves scalability for read-heavy administrative operations by reducing response time from seconds to low single-digit milliseconds and increasing throughput to above 40,000 requests per second. Code-quality metrics further indicate clean module boundaries (CBO=0; LCOM*=0), while the Maintainability Index (MI) highlights modules that require targeted refactoring. Overall, the backend provides a reusable reference architecture for centralized halal tourism administration such as partner verification, content moderation, transaction oversight, and system monitoring that can be adapted to similar platforms in other regions.